The perception of UiTM students towards teaching and learning of Jawi at various levels of education in Malaysia: What should we do to expand its mastery? / Noraziah Mohd Amin, Noor Azam Abdul Rahman and Wan Noorli Razali - Mohd Amin, Noraziah; Abdul Rahman, Noor Azam; Razali, Wan Noorli (Academy of Language Studies, 2019)
The present study was conducted in order to discover the overall perception of the youth which was represented by 79 UiTM Penang Malay students regarding the actions that could be taken to expand the mastery of Jawi at various levels of education in Malaysia. This research employed a quantitative method via the administration of a questionnaire containing 20 items to each respondent involved. The items were designed to answer the research question of the study, “What is the perception of UiTM Penang Malay students towards the initiatives that can be taken in order to expand the teaching and learning of Jawi at various levels of education in Malaysia?” The results revealed that most of the respondents contributed positive views towards the exposure and practice of Jawi at various levels of education and supported some initiatives suggested for expanding the teaching and learning of Jawi. For example, 33 respondents (41.8%, M= 4.24, SD= 0.738) strongly agreed with item 9 (“In my opinion, Jawi subject needs to be offered at all levels of learning (primary, secondary and tertiary levels) so that its learning can be more comprehensive”). Obviously, the respondents in majority favor the teaching and learning of Jawi to the point that they think it should be made a subject that is offered at all educational levels.